New perspectives on Microsoft Office Word 2003 - S. Scott Zimmerman (Thomson Course Technology, 2006)
Part of the New Perspectives series, this text offers a case-based, problem-solving approach and innovative technology for meaningful learning of Microsoft Word 2003 in an introductory course